Development of a Solar Autonomous Boat Navigation Guidance System for Future Swarm Unmanned-Surface-Vehicle Implementation - Denny Darlis; Nurul Fahmi Adani Syam; Aris Hartaman (Jurnal Elektronika dan Telekomunikasi, 2026)
Changes in the quality of the lake environment due to human activities demand efficient and sustainable monitoring solutions. This research designed a navigation guidance system for the solar autonomous boat that operates independently using solar energy and designed as a modular navigation unit to support future swarm-based cooperation between multiple vessels. The system relies on GPS ATGM336H and GY-271 digital compass sensor as positioning and direction determinants, controlled by a TTGO ESP32 LoRa microcontroller. Navigation data is processed in real-time and sent over the LoRa network to a central or intership gateway. This research focuses on the development and validation of the autonomous navigation core, providing the necessary guidance capabilities for integration into a swarm unmanned surface vehicle (USV) framework. The test results showed that the boat could follow the destination's direction with an accuracy of 92%, where most of the trajectory was within the pre-programmed directional tolerance. The average direction error was recorded at 5.4 degrees, within acceptable tolerance limits. The system can adaptively maintain a stable heading and respond to aquatic environmental conditions. By establishing this stable autonomous navigation baseline, the system provides a scalable platform for future swarm implementations aimed at improving large-scale environmental monitoring. This system is considered successful as an intelligent and sustainable autonomous navigation solution.